Application of crop simulation models for water and nutrient management on growth and productivity of rice under different climate scenarios - Sruthi, P (KSCSTE- Centre For Water Resources Development & Management, University of Calicut, 2024)
Rice, the second most vital cereal crop globally, plays a crucial role in culture, lifestyles, and ecosystem services. Despite its significance, challenges such as industrialization, resource constraints, and climate change threaten global food security. This study focuses on rice production in Kerala, where a sharp decline in area and production has been observed over the past 20 years, and given ongoing climate changes, this scenario is anticipated to worsen in the future. The objective of this research was to identify optimal management practices for rice, focusing on water and nutrient requirements to enhance growth and maximize production. This goal was accomplished through a comprehensive approach involving field experiments, crop modelling, and simulation studies. Furthermore, the investigation sought to evaluate the influence of diverse environmental factors on rice growth and production, particularly under varying climate scenarios. The research aims to address this issue by assessing the Crop Simulation Model (CSM) for rice under diverse climatic scenarios and proposing sustainable management practices to improve crop and water productivity. The study outlines seven experiments conducted from 2018 to 2023, focusing on nutrient and water management strategies, post-harvest field management, and greenhouse gas emissions mitigation. Results reveal the impact of different irrigation and nutrient management strategies on rice varieties, emphasizing the importance of optimizing practices for enhanced crop performance and resource conservation. The experiment showed a significant 37.52% water savings through alternate wetting and drying compared to conventional flood irrigation. Additionally, the study explores aerobic rice management techniques as water-saving technologies, providing valuable insights into nutrient and planting strategies, in which Direct Seeding of Rice (DSR) with 125% inorganic fertilizers exhibited superior yield and growth characteristics. The research also examines effective water and nutrient management practices for aerobic rice in midland lateritic soils, highlighting the significance of incorporating cocopeat to combat water stress. Furthermore, experiments evaluating organic management practices demonstrate the potential benefits of combining compost and Azolla for improved crop yield and soil health. Post-harvest field management strategies are explored to mitigate greenhouse gas emissions, with non-winter flooding and late straw incorporation proving effective. Additionally, the DSSAT-CERES Rice model was calibrated and validated for the aerobically grown Uma rice cultivar using field experiment data. The study employs crop simulation models and spatial techniques to simulate crop yield under various management practices, projecting a decline in rice production with increasing temperatures. It also assesses the impact of climate change on paddy farming in Kozhikode and Palakkad districts using temperature data from CMIP6 SSP2-4.5 and SSP5-8.5 scenarios across different models (CMCC-ESM2, EC-Earth3, EC-Earth3-Veg, and GFDL-CM4) for future yield prediction. The findings indicate that climate change is likely to negatively impact paddy yield with a corresponding increase in temperature. The study further highlights potential adaptation measures such as altering sowing dates and optimizing fertilizer management. In conclusion, this research provides valuable insights into site-specific nutrient and water management strategies affecting rice yield and offers recommendations for sustainable agricultural practices. The findings emphasize the need for precision farming, water-efficient technologies, and adaptive strategies to ensure food security and support Kerala’s goal of becoming carbon-neutral by 2050.
Keywords: Rice production; Water and nutrient management; Climate change impact; Crop simulation modelling; Sustainable agriculture